Application of Back Massage Therapy to Prevent Pressure Sores in Patients with Decreased Consciousness: A Case Study - Arifa, Yeni Zanuba; Yunanto, Rismawan Adi (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Patients with neurological disorders, especially those with reduced consciousness, will experience a decrease in their ability to mobilize. Patients who experience decreased ability to mobilize for a long time are at risk of developing pressure sores. The presence of pressure in the protruding bone area causes pressure sores that block blood flow and cause injury to necrosis of the skin tissue. Interventions that nurses can do to improve blood flow to reduce the occurrence of pressure sores, namely by doing back massage. Back massage helps improve circulation in areas where the bones are protruding so that it can prevent pressure sores. This study aimed to explain the effectiveness of the Back Massage Therapy intervention in preventing pressure sores in patients with a decreased level of consciousness. The research method used is a case study with a research time of 3 days with data sources obtained from medical records, assessments, and direct observation of patients. Based on the results of the evaluation before and after the back massage, it showed that there was a change in the condition of the skin before and after the procedure, namely there were no signs of redness, abrasions, bluish or necrosis in the back area and bony prominences. Back Massage can reduce the risk of pressure sores in patients with decreased consciousness.